Possibility of using interdigital sensor (IDS) in estimating different level of blood glucose - Zaharudin, Zarimin; Adam, Ismail; Khan, Sheroz; Nordin, Anis Nurashikin; Gunawan, Teddy Surya (2016)
This paper presents the relationship of an effective capacitance of the interdigital sensor (IDS) with effective relative permittivity (ε_re) of the material under test (MUT). The relationship of the effective capacitance of the interdigital sensor against the relative permivittivity ε_re is examined by using the curve fitting tool provided by MATLAB. Investigation shows there is a promising new technique in using of the IDS for properties of blood detection. The simulation results are presented and discussed.